Preparation method and application of ultrahigh-entropy complex-phase oxide powder material for thermal barrier coating
By introducing 11 rare earth elements into YSZ thermal barrier coating materials and using sol-gel method and discharge plasma sintering technology, ultra-high entropy complex phase oxide powder material was prepared, which solved the high thermal conductivity of YSZ in high temperature environments and the problem of poor chemical stability, higher thermal stability and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411648779.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing thermal barrier coating material YSZ has problems with high thermal conductivity, metastable tetragonal phase degradation and poor sintering resistance under high temperature environments, resulting in the upper limit of its acceptance in long-term use is 1200°C and above 1200°C. It is susceptible to corrosion by CMAS in the environment.
Ultra-high entropy complex oxide powder material was prepared by sol-gel method. By introducing 11 rare earth elements into Y2Ti2O7 with calcined stone structure, and using discharge plasma sintering technology, it formed with low thermal conductivity and high chemical stability. Ceramic material.
Maintain phase stability around 1500°C, reduce thermal conductivity, improve chemical stability and mechanical properties, extend thermal cycle life, and enhance anti-sintering performance.
Smart Images

Figure CN119462181A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ultra-high entropy multiphase oxide materials, and in particular to a preparation method and application of an ultra-high entropy multiphase oxide powder material for a thermal barrier coating. Background Art
[0002] Thermal barrier coatings (TBC) are ceramic coatings with good thermal insulation properties in high temperature environments. They are widely used in the hot end components of ground-based gas turbines and aircraft engines to provide thermal protection and prevent damage to the engine caused by oxidation, corrosion and erosion. The hot end components are subjected to extreme conditions of high temperature, high pressure and high speed during service, and any failure may lead to serious consequences. At present, the most commonly used thermal barrier coating material is Y2O3-stabilized ZrO2 ceramic (Yttria-Stabilized Zirconia, YSZ), which has a high thermal expansion coefficient, high fracture toughness and excellent thermal shock resistance. However, YSZ also has some significant technical difficulties, such as high thermal conductivity, metastable tetragonal phase degradation and poor sintering resistance, resulting in its upper limit of acceptance in long-term use being 1200℃. In addition, at temperatures exceeding 1200℃, melted CMAS (CaO, Al2O3, SiO2 and other sand and dust) will enter the coating and react with Y2O3, causing the stabilizer to fail, thereby accelerating the failure of the YSZ coating. Therefore, research on new thermal barrier coating materials has become the key to improving engine efficiency. Pyrochlore-structured A2B2O7 ceramic materials, such as La2Zr2O7, have become important candidate materials due to their low thermal conductivity, low oxygen permeability, excellent high-temperature stability and sintering resistance. However, La2Zr2O7 ceramics have a low thermal expansion coefficient (9.1×10^–6K^–1, 1000℃) and low fracture toughness (1.4MPam^1 / 2), resulting in an unsatisfactory thermal cycle life of the coating, which still needs further improvement.
[0003] In response to the above problems, we have introduced a preparation method and application of ultra-high entropy multiphase oxide powder material for thermal barrier coatings. Summary of the invention
[0004] The invention discloses a preparation method of an ultra-high entropy multiphase oxide powder material for a thermal barrier coating and application thereof, aiming to solve the technical problems in the background technology.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing an ultra-high entropy multiphase oxide powder material for a thermal barrier coating comprises the following steps:
[0007] S1. Evenly dispersing a rare earth element source and a transition metal element source in deionized water, stirring at 80° C., and then adding a complexing agent and a dispersant to obtain a mixture A;
[0008] S2. Under stirring at 80° C., adjusting the pH of the mixture A system to 4-5 with aqueous ammonia, continuing stirring to form a gel, and drying to obtain a xerogel;
[0009] S3. Sintering the dry gel at 1400° C. for 2 h to obtain an ultra-high entropy composite oxide powder material.
[0010] The components of the rare earth elements are La3+, Ce3+, Pr3+, Nd3+, Sm3+, Eu3+, Gd3+, Dy3+, Er3+, Yb3+, and Y3+;
[0011] The component of the transition metal element is Ti4+;
[0012] The rare earth elements are introduced in equimolar amounts.
[0013] The total molar amount of the rare earth element and the transition metal element are introduced in an equimolar amount, and the introduced amount is allowed to fluctuate by 10% within the equimolar ratio.
[0014] The rare earth element sources are La(NO3)3·6H2O, Ce(NO3)3·6H2O, Pr(NO3)3·6H2O, Nd(NO3)3·6H2O, Sm(NO3 )3·6H2O, Eu(NO3)3·6H2O, Gd(NO3)3·6H2O, Dy(NO3)3·6H2O, Er(NO3)3·6H2O, Yb(NO3)
[0015] 3·6H2O, Y(NO3)3·6H2O, and the transition metal element source is C16H36O4Ti.
[0016] The ratio of the total molar amount of metal cations of the rare earth element source and the transition metal element source to deionized water is 0.8-1.2 mol:1L.
[0017] The ratio of the total molar amount of the metal elements in the rare earth element source to the total molar amount of the metal elements in the transition metal element source is 1:1±0.1, and the molar amount of each metal element in the rare earth element source is equal.
[0018] The complexing agent is citric acid, and the dispersing agent is polyethylene glycol.
[0019] The ratio of the total molar amount of metal cations of the rare earth element source and the transition metal element source to the molar amount of citric acid is 1:2, and the added amount of polyethylene glycol is 10% of the mass of the mixture A.
[0020] An application of an ultra-high entropy complex phase oxide powder material for a thermal barrier coating comprises the following steps: grinding the ultra-high entropy complex phase oxide powder material, wherein the main phase is a pyrochlore structure and the second phase is a fluorite structure, using an agate mortar and sieving using a 300-mesh sieve to obtain an ultra-high entropy complex phase oxide powder with fine and uniform particle size; loading the ground and sieved ultra-high entropy oxide powder into a graphite mold, and performing discharge plasma sintering at 30 MPa and 1500° C. for 15 min to obtain a ceramic block material.
[0021] The preparation method of an ultra-high entropy multiphase oxide powder material for a thermal barrier coating and its application provided by the present invention have the following advantages:
[0022] 1. According to the service requirements of thermal barrier coatings, the present invention designs a new ultra-high entropy composite oxide ceramic material suitable for thermal insulation coatings of hot end components of aircraft engines. The sol-gel method is used to complete the synthesis of the new material powder, and the technology of spark plasma sintering is proposed to complete the preparation of thermal barrier coating test materials. This new material makes up for the shortcomings of traditional thermal barrier coating YSZ materials, can still maintain phase stability at around 1500°C, and expands the thermal barrier coating material system to the field of ultra-high entropy composite ceramics;
[0023] 2. The present invention introduces 11 rare earth elements into the pyrochlore structure of Y2Ti2O7, skipping the high entropy system and directly expanding the traditional single rare earth titanate ceramics to the ultra-high entropy ceramic system (12 principal elements) to complete the design and preparation of ultra-high entropy pyrochlore oxide ceramics. A large number of cations of different radii cause the material to undergo very obvious lattice distortion, reducing the mean free path of phonon propagation inside it, increasing phonon scattering, and greatly reducing the thermal conductivity of this high entropy oxide material. The high entropy oxide has high thermal stability and very low thermal conductivity in a high temperature environment, and still maintains a stable phase structure in a high temperature environment, and the grain growth phenomenon is not obvious. At the same time, it also causes ion diffusion hysteresis, increases atomic migration energy and diffusion energy, and greatly improves the chemical stability of this high entropy oxide material;
[0024] 3. The present invention generates a second phase in situ by oxidation of Ce3+. Under high temperature and thermal shock, the second phase undergoes phase transformation and precipitates in a granular form, releasing thermal stress and avoiding crack initiation, thus making up for the poor fracture toughness of the ceramic material itself and achieving a self-toughening effect.
[0025] 4. The present invention selects rare earth elements La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Er, Yb, transition metal element Y and the like as components of ultra-high entropy oxides. When each element exists alone as an oxide, it has excellent properties such as high thermal stability, good mechanical properties, corrosion resistance, stable chemical properties, and radiation resistance. The ultra-high entropy oxides synthesized by the present invention have further improved mechanical properties, physical properties, chemical properties, etc.;
[0026] 5. The present invention uses the sol-gel method to synthesize ultra-high entropy complex phase oxide powder materials. The oxide synthesized by this method has the characteristics of uniform element distribution, small and uniform powder particle size, high purity, etc., and this method has low equipment requirements and a simple synthesis method. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a schematic flow chart of a method for preparing ultra-high entropy multiphase oxide powder material for thermal barrier coating.
[0028] Figure 2 This is a physical photograph of the ultra-high entropy complex oxide powder material prepared in the embodiment of the present invention.
[0029] Figure 3 It is an X-ray diffraction spectrum of the ultra-high entropy complex phase oxide powder material prepared in an embodiment of the present invention.
[0030] Figure 4 This is a backscattered scanning electron microscope photograph of the ultra-high entropy oxide block prepared in an embodiment of the present invention.
[0031] Figure 5 It is a scanning electron microscope secondary electron photograph and energy spectrum distribution diagram of the ultra-high entropy oxide block prepared in an embodiment of the present invention after high-temperature treatment at 1500°C.
[0032] Figure 6 This is an X-ray diffraction pattern of the ultra-high entropy oxide block prepared in an embodiment of the present invention after a thermal shock test at 1200°C.
[0033] Figure 7 This is a scanning electron microscope secondary electron photograph of the ultra-high entropy oxide block prepared in an embodiment of the present invention after a thermal shock test at 1200°C. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application usually described and marked in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the application claimed for protection, but merely represents the selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application.
[0035] Example
[0036] A method for preparing ultra-high entropy multiphase oxide powder material:
[0037] The rare earth element sources La(NO3)3·6H2O, Ce(NO3)3·6H2O, Pr(NO3)
[0038] 3·6H2O, Nd(NO3)3·6H2O, Sm(NO3)3·6H2O, Eu(NO3)3·6H2O, Gd(NO3)3·6H2O, Dy(NO3)3·6H2O, Er(NO3)3·6H2O, Yb(NO3)
[0039] 3·6H2O, Y(NO3)3·6H2O) and a transition metal source (C16H36O4Ti) are uniformly dispersed in deionized water to form a homogeneous solution with a concentration of 1 mol / L, wherein the molar ratio of each rare earth source is 1:1, and the ratio of the total molar amount of the rare earth source to the total molar amount of the transition metal source is 1:1±0.1. Subsequently, the mixture is stirred at 80°C at a stirring speed of 300rpm, and then a complexing agent (citric acid) and a dispersant (polyethylene glycol) are added during the stirring process to obtain a mixture A; wherein the ratio of the total metal cation molar amount of the rare earth source and the transition metal source to the molar amount of citric acid is 1:2, and the amount of polyethylene glycol added is 10% of the mass of the mixture A. Impurities introduced by citric acid and polyethylene glycol can be removed in the subsequent sintering process. Under stirring at 80°C, add a 15%wt ammonia solution to the mixture A system to adjust the pH of the system to 4-5, continue stirring at 80°C, and continue to evaporate water until all metal cations are completely complexed to form a gel state. Put the gel into an oven again and dry it at 150°C for 24 hours to obtain a dry gel. The impurity ions introduced by the ammonia solution can be removed in the subsequent sintering process. Finally, the dry gel is sintered at 1400°C for 2 hours to obtain an ultra-high entropy complex oxide powder material with a powder particle size uniformly distributed in the range of 0.1-1μm.
[0040] An application of an ultra-high entropy complex phase oxide powder material for a thermal barrier coating comprises the following steps: grinding the ultra-high entropy complex phase oxide powder material, wherein the main phase is a pyrochlore structure and the second phase is a fluorite structure, using an agate mortar and sieving using a 300-mesh sieve to obtain an ultra-high entropy complex phase oxide powder with fine and uniform particle size; loading the ground and sieved ultra-high entropy oxide powder into a graphite mold, and performing discharge plasma sintering at 30 MPa and 1500° C. for 15 min to obtain a ceramic block material.
[0041] 1. Powder photos
[0042] The actual photo of the ultra-high entropy multiphase oxide powder material prepared in Example 1 of the present invention is as follows: Figure 2 shown.
[0043] 2. X-ray diffraction test
[0044] The ultra-high entropy multiphase oxide powder prepared in Example 1 of the present invention was subjected to an X-ray diffraction test, and the results are as follows: Figure 3 As shown. Figure 3 It can be seen that the main phase of the prepared ultra-high entropy oxide powder is a typical pyrochlore phase, and the second phase is a CeO2 fluorite phase.
[0045] 3. Scanning electron microscope test
[0046] Taking the ceramic block prepared in Example 2 of the present invention as an example, the obtained object was tested by scanning electron microscope, and the results are as follows: Figure 4 and Figure 5 shown. Figure 4 This is a backscattered scanning electron microscope photograph of Example 2. It can be seen that the ultra-high entropy oxide ceramic block prepared in Example 2 of the present invention is dense, has a low porosity, and the second phase is uniformly distributed in the matrix in strips. Figure 5 This is a scanning electron microscope secondary electron photograph and energy spectrum distribution diagram of Example 2 after high-temperature treatment at 1500°C. It can be seen that after high-temperature treatment, the second phase precipitates in a granular form, and the precipitate is enriched in the Ce element.
[0047] 4. Thermal stability and thermal shock resistance test
[0048] Taking the ceramic block prepared in Example 2 of the present invention as an example, the thermal stability and thermal shock resistance of the obtained object were tested at 1200°C. The results are as follows: Figure 6 and Figure 7 shown. Figure 6 These are the X-ray diffraction results after 50 and 125 thermal shocks. It can be seen that the phase structure of the sample remains stable after 125 thermal shocks. Figure 7These are secondary electron photographs of the scanning electron microscope after different numbers of thermal shocks. It can be seen that the second phase gradually precipitates in the form of particles after the thermal shock, releasing the thermal stress, and no cracks appear in the sample.
[0049] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. The replacement may be a replacement of a part of the structure, device, method step, or a complete technical solution. Any equivalent replacement or change according to the technical solution and the inventive concept of the present invention shall be covered within the protection scope of the present invention.
Claims
1. A method for preparing an ultra-high entropy multiphase oxide powder material for a thermal barrier coating, characterized in that: The steps include: S1. Evenly dispersing a rare earth element source and a transition metal element source in deionized water, stirring at 80° C., and then adding a complexing agent and a dispersant to obtain a mixture A; S2. Under stirring at 80° C., adjusting the pH of the mixture A system to 4-5 with aqueous ammonia, continuing stirring to form a gel, and drying to obtain a xerogel; S3. Sintering the dry gel at 1400° C. for 2 h to obtain an ultra-high entropy composite oxide powder material.
2. The method for preparing the ultra-high entropy multiphase oxide powder material for thermal barrier coating according to claim 1, characterized in that: The components of the rare earth elements are La3+, Ce3+, Pr3+, Nd3+, Sm3+, Eu3+, Gd3+, Dy3+, Er3+, Yb3+, and Y3+; The component of the transition metal element is Ti4+; The rare earth elements are introduced in equimolar amounts.
3. The method for preparing the ultra-high entropy multiphase oxide powder material for thermal barrier coating according to claim 1, characterized in that: The total molar amount of the rare earth element and the transition metal element are introduced in an equimolar amount, and the introduced amount is allowed to fluctuate by 10% within the equimolar ratio.
4. The method for preparing the ultra-high entropy multiphase oxide powder material for thermal barrier coating according to claim 1, characterized in that: The rare earth element source is La(NO3)3·6H2O, Ce(NO3) 3·6H2O, Pr(NO3)3·6H2O, Nd(NO3)3·6H2O, Sm(NO3)3·6H2O, Eu(NO3)3·6H2O, Gd(NO3)3·6H2O, Dy(NO3)3·6H2O, Er(NO3) 3·6H2O, Yb(NO3)3·6H2O, Y(NO3)3·6H2O, and the transition metal element source is C16H36O4Ti.
5. The method for preparing an ultra-high entropy multiphase oxide powder material for a thermal barrier coating according to claim 1, characterized in that: The ratio of the total molar amount of metal cations of the rare earth element source and the transition metal element source to deionized water is 0.8-1.2 mol:1L.
6. The method for preparing the ultra-high entropy multiphase oxide powder material for thermal barrier coating according to claim 1, characterized in that: The ratio of the total molar amount of the metal elements in the rare earth element source to the total molar amount of the metal elements in the transition metal element source is 1:1±0.1, and the molar amount of each metal element in the rare earth element source is equal.
7. The method for preparing an ultra-high entropy multiphase oxide powder material for thermal barrier coating according to claim 1, characterized in that: The complexing agent is citric acid, and the dispersing agent is polyethylene glycol.
8. The method for preparing the ultra-high entropy multiphase oxide powder material for thermal barrier coating according to claim 1, characterized in that: The ratio of the total molar amount of metal cations of the rare earth element source and the transition metal element source to the molar amount of citric acid is 1:2, and the added amount of polyethylene glycol is 10% of the mass of the mixture A.
9. An application of ultra-high entropy multiphase oxide powder material for thermal barrier coating, characterized in that: According to the preparation method according to any one of claims 1 to 9, an ultra-high entropy complex phase oxide powder material, whose main phase is a pyrochlore structure and whose second phase is a fluorite structure, is ground using an agate mortar and sieved using a 300-mesh sieve to obtain an ultra-high entropy complex phase oxide powder with fine and uniform particle size, the ground and sieved ultra-high entropy oxide powder is filled in a graphite mold, and spark plasma sintering is performed at 30 MPa and 1500° C. for 15 min to obtain a ceramic block material.
Citation Information
Patent Citations
Fluorite structure high-entropy oxide powder for thermal barrier coating and preparation method of fluorite structure high-entropy oxide powder
CN113023776A
CMAS-corrosion-resistant multi-component high-entropy pyrochlore structure thermal barrier coating material and preparation method and application thereof
CN113772723A
High-entropy oxide ceramic with ten-element brown yttrium niobium ore structure and preparation method of high-entropy oxide ceramic
CN114685165A
High-entropy oxide powder material for thermal barrier coating as well as preparation method and application of high-entropy oxide powder material
CN114920559A
High-entropy oxide powder material, radioactive waste solidification base material and preparation method
CN116332638A